2021
DOI: 10.9745/ghsp-d-20-00422
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Study of Factors Influencing Access to and Use of Micronutrient Powders in Rwanda

Abstract: In Rutsiro district, the unavailability of multiple micronutrients powder (MNP) was mentioned as a major barrier to accessing it. Factors that appeared to limit the use of MNP included perceived side effects and the perceptions that MNP is designed for undernourished children, coupled with inappropriate child feeding practices, particularly feeding thin/watery complementary foods.n Mothers of older children (aged 12-23 months) had about 4 times higher odds of using MNP than mothers of younger children (aged 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A regional study in Rwanda reveals that, while 64% of mothers had given micronutrients to their children, only 38% had done so over the preceding seven days (Dusingizimana et al, 2021). recognized, evaluating actual compliance to these interventions and quantifying the explicit costs of any corrective measure would require field research which is beyond the scope of this article.…”
Section: Behavioural Changementioning
confidence: 99%
“…A regional study in Rwanda reveals that, while 64% of mothers had given micronutrients to their children, only 38% had done so over the preceding seven days (Dusingizimana et al, 2021). recognized, evaluating actual compliance to these interventions and quantifying the explicit costs of any corrective measure would require field research which is beyond the scope of this article.…”
Section: Behavioural Changementioning
confidence: 99%
“…In several countries, unavailable MNP was generated by a lack of local suppliers and unstable supply chains. Several studies also cited that adequate allocation of financial and human resources was essential but limited in many countries [12,23,29,30,40,45,46,50,52]. For example, primarylevel workers were often too busy to perform intervention activities.…”
Section: Domain 3: Inner Settingmentioning
confidence: 99%
“…The most common driving factor was the good coordination of the MNP program within the health system. Relying on the primary health care system, primary-level workers undertook the tasks of MNP distribution, social and behavior change communication (SBCC), and program monitoring (such as making regular visits to evaluate if MNPs were used correctly and effectively) [3,20,31,39,[44][45][46][52][53][54]. In this way, the users were more receptive to interventions considering the authority of primary-level workers.…”
Section: Domain 3: Inner Settingmentioning
confidence: 99%
“…The article by Dusingizimana et al 14 in this issue of Global Health: Science and Practice documents the performance of an MNP program in Rwanda. As they report, MNPs have been implemented in Rwanda with support from United Nations Children's Fund (UNICEF) and other partners.…”
Section: What About Micronutrient Powders As a Strategy For Addressing Micronutrient Deficiencies In Infants And Young Children?mentioning
confidence: 99%
“…In this study, 14 program performance was assessed in Rutsiro district, 1 of 19 in the first wave of scale-up. The district was selected for this study primarily because it was found to have a particularly poor baseline nutrition status.…”
Section: What About Micronutrient Powders As a Strategy For Addressing Micronutrient Deficiencies In Infants And Young Children?mentioning
confidence: 99%